KONSTRUKSI TASYRI PADA MASA LAHIRNYA MAZHAB FIKIH - Rusdiyah Rusdiyah (Universitas Islam Negeri Antasari Banjarmasin, 2014)
The Islamic law of today has the relationship with the past Islamic law. In the history process, the growth and development of Islamic law show a dynamics of religious though and describe the clash of religious and the development of social and cultural where the law grows. Therefore, is it appropriate if there is a view that Islamic law is something sacred, immutable and rigid. History fact, especially Islamic law in the golden era, will give a reality about tasyri construction or Islamic law legislation and about emergence of mazhab.